Konversi Bank Riau Kepri Menjadi Bank Riau Kepri Syariah - S, Suharyono (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of banking in Indonesia has begun to increase as shown by the increasing number of Islamic banks in Indonesia. This study aims to find out how physiological influences, attention, interests, unidirectional needs, knowledge and customer moods have on the conversion of Bank Riau Kepri to Bank Riau Kepri Syariah. This research uses quantitative methods. Data collection through distributing questionnaires and accompanied by documentation. The technique for determining the number of samples uses a sample table according to Sugiyono (2017), namely 383 customers of Bank Riau Kepri Syariah. The research used an accidental sampling technique to determine the sample. Data processing techniques using the SPSS (Statistical Product and Service Solution) 23 program, where the data analysis used in this study consisted of validity tests, reliability tests, normality tests, multicollinearity tests, autocorrelation tests, partial correlation coefficient tests, determination coefficient tests, t test and f test . The results showed that physiological customers (X1) had a significant positive effect on the conversion of Bank Riau Kepri to Bank Riau Kepri Syariah, customer attention (X2) had a significant positive effect on the conversion of Bank Riau Kepri to Bank Riau Kepri Syariah, customer interest (X3) had a significant positive effect on the conversion of Bank Riau Kepri to Bank Riau Kepri Syariah, needs that are in the same direction as the customer (X4) have a significant effect on the conversion of Bank Riau Kepri to Bank Riau Kepri Syariah, customer knowledge (X5) has a significant positive effect on the conversion of Bank Riau Kepri to Bank Riau Kepri Syariah, customer mood (X6) has a significant positive effect on the conversion of Bank Riau Kepri to Bank Riau Kepri Syariah.